The innovation of spinal endoscopy: one-hole bi-medium endoscopy for decompression and fusion in the treatment of lumbar degenerative diseases - Cui, Xingang; Li, Hengren; Jing, Xingzhi; Jia, Fei; Liu, Xiaoyang (Frontiers in Surgery, 2025)
The spinal endoscopy technique has been widely used in the treatment of lumbar, thoracic, and cervical diseases over the past 20 years. Minimally invasive decompression, assisted by fixation and interbody fusion, is the optimal treatment for lumbar degenerative diseases, such as lumbar spondylolisthesis and lumbar spinal stenosis. Although endoscopic lumbar spinal interbody fusions have been reported, further evaluation of their effectiveness and efficacy is necessary. We innovated the spinal endoscopy technique called the one-hole bi-medium endoscopy (OBE) technique, in which lumbar interbody fusion, pedicle screw fixation, and bilateral decompression are completed through one incision under endoscopic visualization with or without liquid irrigation. The visual analog scale and Oswestry disability index scores were significantly improved after the OBE treatment. Our study concludes that the OBE procedure can simultaneously realize decompression and fusion and is effective in the treatment of lumbar diseases.